The metamorphosed mafic-ultramafic complex of Mokuro, Ilesha Schist Belt, southwestern Nigeria - Schmädicke, Esther; et al. (Journal of African Earth Sciences, 1998)
In the Proterozoic Schist Belt of Nigeria, lenticular bodies of metabasites and meta-ultramafics are frequently intercalated within staurolite bearing metapelitic schists. Such a metamorphosed mafic-ultramafic complex is particularly well exposed in the Mokuro riverbed between the towns of Ife and Ilesha. These outcrops display contact relationships with the surrounding metasediments, as well as between the individual mafic and ultramafic rock types. The most common mafic rocks are indistinctly layered amphibolites, accompanied by apatite rich amphibolites and massive amphibolites, in part rich in ilmenite and pyrrhotite. Among the generally massive ultramafic rocks, nearly monomineralic amphibole rocks predominate, while chlorite-amphibole, talc-chlorite-amphibole and talc bearing olivine-chlorite-amphibole rocks occur in subordinate amounts. Field, textural and geochemical evidence suggest that mafic-ultramafic complex derived from a thick, structurally differentiated basaltic sill that contained doleritic portions in its interior. Slow cooling rates in these inner parts enabled crystal settling with the formation of ultramafic cumulates. Due to the enrichment of volatiles during the crystallization process, higher amounts of apatite and sulphides, as well as late magmatic amphibole, were formed in parts of the mafic-ultramafic body. Mineral assemblages in the mafic-ultramafic complex testify to a metamorphic overprint under amphibolite-facies conditions. Thermodynamic modelling in the system CMFASH leads to an estimated P-T range of 1.5-3 kbar and 550-620°C for the metamorphic peak assemblage talc-olivine-chlorite-Ca amphibole-orthoamphibole.
UnivIS-Import:2017-03-24:Pub.1998.nat.dgeo.IGM.profes_1.themet